2020
DOI: 10.3390/su12187383
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Design Classes for Environmental Sustainability of Interior Architectural Design

Abstract: The paper considers the adjustments of the interior architectural design education model toward its compliance with the principles of sustainability, since the currently provided scheme does not effectively employ the sustainability multi-dimensional concept as a substantial determinant of interior architectural design. The conventional interior architectural design curriculum requires corrections, to provide students with systematized knowledge on sustainability issues, as well as appropriate abilities and sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Several researchers [18][19][20][21][22] have identified specific skills necessary for successful and sustainable design across engineering disciplines and architecture, and these skills include the ability to (a) tolerate ambiguity through a divergent-convergent thinking process, (b) think in terms of a bigger picture, (c) handle uncertainty, (d) make decisions, (e) think as part of a team in a social process, and (f) think and communicate in several languages of design. It was also found that architecture students with a developed ability for design thinking to solve architecture problems were more likely to take it as a challenge to collect the users' input during the problem-solving process and the solutions they generated from the users' concerns and needs were more diverse, more imaginative, and more feasible [7,14]. It could be interesting to explore the ways of architecture design articulation, towards SDGs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Several researchers [18][19][20][21][22] have identified specific skills necessary for successful and sustainable design across engineering disciplines and architecture, and these skills include the ability to (a) tolerate ambiguity through a divergent-convergent thinking process, (b) think in terms of a bigger picture, (c) handle uncertainty, (d) make decisions, (e) think as part of a team in a social process, and (f) think and communicate in several languages of design. It was also found that architecture students with a developed ability for design thinking to solve architecture problems were more likely to take it as a challenge to collect the users' input during the problem-solving process and the solutions they generated from the users' concerns and needs were more diverse, more imaginative, and more feasible [7,14]. It could be interesting to explore the ways of architecture design articulation, towards SDGs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Designers cope with the probability of solution or design realisation when the rule is set, while result and example are very often subject to a trade-off in an extensive decision-making process. This points to a higher level of student motivation, productivity, and engagement if they want to address complex design tasks, and shapes innovative behaviour needed for sustainable architecture [14]. An affective commitment and intrinsic motivation can be the key to success in the design-based activities of architecture students.…”
Section: Self-directed Learning and Design Thinkingmentioning
confidence: 99%
See 3 more Smart Citations